2014
DOI: 10.1002/ece3.1213
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific winter distribution in a sexually dimorphic shorebird is explained by resource partitioning

Abstract: Sexual size dimorphism (SSD) implies correlated differences in energetic requirements and feeding opportunities, such that sexes will face different trade-offs in habitat selection. In seasonal migrants, this could result in a differential spatial distribution across the wintering range. To identify the ecological causes of sexual spatial segregation, we studied a sexually dimorphic shorebird, the bar-tailed godwit Limosa lapponica, in which females have a larger body and a longer bill than males. With respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Although sex segregation alone is unlikely to explain the patterns we observe (it could only lead to 2 types of routes), it may be a contributing factor. Sex segregation has been observed in many sexually size-dimorphic species ( Brown et al 1995 ; Carbone and Owen 1995 ; Stewart 1997 ; Catry et al 2004 ; Duijns et al 2014 ) including seabirds ( Croxall et al 2005 ; Phillips et al 2009 , 2011 ), but examples in monomorphic species are rare ( Bogdanova et al 2011 ; Guilford et al 2012 ; Müller et al 2014 ) and the causes behind the segregation are unclear. Although we did not find any sex differences between sexually monomorphic puffins following different types of routes, we found some spatial sex segregation and sex differences in the birds’ distance from the colony.…”
Section: Discussionmentioning
confidence: 99%
“…Although sex segregation alone is unlikely to explain the patterns we observe (it could only lead to 2 types of routes), it may be a contributing factor. Sex segregation has been observed in many sexually size-dimorphic species ( Brown et al 1995 ; Carbone and Owen 1995 ; Stewart 1997 ; Catry et al 2004 ; Duijns et al 2014 ) including seabirds ( Croxall et al 2005 ; Phillips et al 2009 , 2011 ), but examples in monomorphic species are rare ( Bogdanova et al 2011 ; Guilford et al 2012 ; Müller et al 2014 ) and the causes behind the segregation are unclear. Although we did not find any sex differences between sexually monomorphic puffins following different types of routes, we found some spatial sex segregation and sex differences in the birds’ distance from the colony.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, spatial segregation between the sexes has been observed (Smith & Evans ; Both, Edelaar & Renema ; Duijns et al . ). These sexual differences in habitat and diet result in females foraging on large deeply buried prey, and females also being more vulnerable to behavioural prey depression than males (Duijns & Piersma ).…”
Section: Methodsmentioning
confidence: 97%
“…During the non-breeding season males feed mainly on small prey items and females predominantly forage on lugworms (Scheiffarth 2001;Duijns & Piersma 2014). Additionally, spatial segregation between the sexes has been observed (Smith & Evans 1973;Both, Edelaar & Renema 2003;Duijns et al 2014b). These sexual differences in habitat and diet result in females foraging on large deeply buried prey, and females also being more vulnerable to behavioural prey depression than males (Duijns & Piersma 2014).…”
Section: Study Systemmentioning
confidence: 99%
“…Several mechanisms have been proposed, including latitudinal differences in foraging conditions, predation risk, inter and intra-specific competition and climate. Prey burying depth and variation in bill length were shown to drive differential migration in Western Sandpipers ( Calidris mauri ), Black-tailed Godwits ( Limosa limosa ) and Bar-tailed Godwits ( Limosa lapponica ) ( Mathot, Smith & Elner, 2007 ; Catry et al, 2012 ; Duijns et al, 2014 ). Choice of non-breeding sites in birds is also affected by latitudinal variation in predation risk ( Nebel & Ydenberg, 2005 ; Díaz et al, 2013 ), as was shown for Western Sandpipers for which predator escape performance was one of the factors correlating with segregation between and within sexes at non-breeding sites ( Nebel & Ydenberg, 2005 ).…”
Section: Introductionmentioning
confidence: 99%